Realizing the Trinity of Pancasila Justice: A Socio-Legal Study of a Community-Based Conflict Resolution - Ahmad Saparwadi; FX Joko Priyono; Ro’fah Setyowati (Faculty of Law, Mulawarman University, 2025)
Public conflicts involving both religious and economic sentiments, such as the case of the